Factors associated with risk and safe sexual behaviour among homosexual men: a review - Filip, Elvira Ventura (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Since the recognition ofthe Aids epidemie homo-sexual men have been highly affected by HIV infec-tion. A large number of studies have examined pos-sible factors associated with sexual risk behaviour within this group. ln this review some of these fac-tors such as demographic, psycho-social, and situ-ational and behavioural factors are reported.